NILAI-NILAI AGAMA SEBAGAI LANDASAN KEPEMIMPINAN - I Nyoman Pancaria (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2019)
The mind that causes man to be bound and the mind also causes man to attain liberation. In our lives the mind as Mobilizer and deciding in every action. If the mind condition is unstable and people can not control his mind then the element of Sad Ripu in Will master us and if we are able to control our minds then we will be able to reach Dasa Dharma or Dasa Sila so happiness We will be able to accomplish